3D-printing in orthopedic dentistry (literature review) - Huryn П. О.; Bida В. І.; Vasiliev М. О. (Actual Dentistry, 2025)
Introduction. Dental prosthetics is one of the most important areas of dentistry, and it is related to replacing a lost tooth/tooth with the help of artificial dental devices. To solve the problems of the traditional molding and closed stamping process, 3D printing is currently considered a new candidate for the manufacture of customized dental products, which is attracting more and more attention worldwide. All consumables for 3D printing in dentistry are divided into polymer materials, photopolymer resins, ceramics, and metals. The advantages of 3D- printing include the production of desired prostheses and models with the least amount of material and the ability to create several products simultaneously. With the help of a 3D printer in dentistry, the following are made: surgical templates for implantation, brace prostheses, crowns, implants, models of jaws for demonstration, plaster products, forms for casting teeth, thin wax models, dental casts, bridge prostheses; casts of partial dentures, orthodontic casts, and devices, dental models, constructions for orthodontics. Goal. Based on a thorough analysis of literary sources, study the main methods of 3D-printing in orthopedic dentistry as part of digital medical technologies. Materials and methods. Scientific sources were searched and analyzed using scientometric databases: Web of Science, PubMed, Google Scholar, ScienceDirect.com (Science, health, and medical journals), and ResearchGate recently. Conclusion. Recent literature analysis has indicated that dentists are interested in developing and applying 3D-printing methods for dental prosthetics, which have significant advantages over traditional technologies.